Multidimensional Formative Context of Conceptual Design: The Method of Inversion - Gasem, Amina; Lahoda, Oksana (HUDPROM: The Ukrainian Art and Design Journal, 2024)
This article explores conceptual design in clothing, focusing on the key aspects of the formative process in fashion design and the artistic-compositional application of deconstruction techniques, particularly the method of inversion. It examines various interpretations and distinctive characteristics of inversion in design practices from a conceptual perspective. Several types of inversions are identified, differing in their execution and application within fashion design. An analysis of contemporary clothing collections reveals that decorative inversion manifests through the rearrangement of individual garment components, technological processing, and decorative or textural elements, which, in this case, serve as the primary design concept. Meanwhile, the constructive method of inversion showcases an experimental approach to structural development within conceptual design. Through this technique, new garment forms emerge as designs evolve via the rearrangement and recombination of pattern fragments. The article discusses and illustrates the distinctive features of both decorative and constructive inversion as applied in the works of renowned fashion brands such as Mason Jung, Martin Margiela, Rick Owens, and Junya Watanabe. The study’s scientific novelty lies in its systematic examination of the deconstructive method of inversion within the framework of conceptual design and its specific applications in fashion.